Alzheimer Disease-associated Cortical Atrophy Does not Differ Between Chinese and Whites. (July 2019) - Fan, Jia; Tse, Marian; Carr, Jessie S.; Miller, Bruce L.; Kramer, Joel H.; Rosen, Howard J.; Bonham, Luke W.; Yokoyama, Jennifer S.
Abstract : Purpose: To assess whether there are differences in Alzheimer disease (AD)-associated atrophy regions in Chinese and white patients with AD versus cognitively normal older adults, and to test whether associations between clinical severity and gray matter volume are similar or different across these ethnic groups in a cross-sectional analysis. Materials and Methods: Chinese and white patients with AD, individuals with mild cognitive impairment, and cognitively normal controls (46 white and 48 Chinese) were clinically evaluated at an academic center within 1 year of magnetic resonance imaging acquisition. Clinical severity was assessed using the Clinical Dementia Rating Sum of Boxes and cortical atrophy was measured using voxel-based morphometry as well as Freesurfer. Chinese and white cohorts were demographically matched for age, sex, and education. Results: Clinical severity by diagnosis was similar across ethnicities. Chinese and white patient groups showed similar amounts of atrophy in the regions most affected in AD after accounting for demographic variables and head size. There was no significant difference between ethnic groups when compared by atrophy and clinical severity. Conclusions: Our study suggests that Chinese and white patients with AD, when matched demographically, are clinically and neuroanatomically similar on normalized measures of cortical atrophy and clinical severity. Abstract : Supplemental Digital Content is available in the text.